The Potential Role of Surprisal in Predicting Pronunciation Problems in L2 English Phonology - Monika Pukli (Anglophonia)
This paper investigates whether phonological properties of articulation complexity coupled with familiarity and frequency of learner usage can explain pronunciation mistakes in L2 English. In an analogy of the (native) phonologization model by Hume and Mailhot (2013), it was expected that one would encounter more mistakes in high surprisal words (i.e. uncommon words whose articulation is complex) than more familiar, average surprisal words, and that low surprisal words (i.e. the most frequent and simple words) would be likewise more often mispronounced than the average. The analysis of pronunciation mistakes in French speakers of English does not indicate a significant correlation between word surprisal categories (low/mid/high) and the presence of errors. Results show that speakers do make mistakes in very high surprisal words but not systematically, while very low surprisal words are rarely mispronounced. The main finding, however, is the irregular relationship between the CEFR levels of lexical forms and the number of errors: unsurprisingly, the category with the most problems is C2 (encompassing archaic and unfamiliar words), but as for the other five categories, the number of mistakes decreases as we move from the easiest A1 level words to the more difficult C1 level words.